Longitudinal impact of two universal preventive interventions in first grade on educational outcomes in high school. - Catherine P. Bradshaw; Jessika H. Zmuda; Sheppard G. Kellam; Nicholas S. Ialongo (2009)
This study examined the longitudinal effects of 2 first-grade universal preventive interventions on academic outcomes (e.g., achievement, special education service use, graduation, postsecondary education) through age 19 in a sample of 678 urban, primarily African American children.The classroom-centered intervention combined the Good Behavior Game (H.H. Barrish, Saunders, & Wolfe, 1969) with an enhanced academic curriculum, whereas a second intervention, the Family-School Partnership, focused on promoting parental involvement in educational activities and bolstering parents' behavior management strategies.Both programs aimed to address the proximal targets of aggressive behavior and poor academic achievement.Although the effects varied by gender, the classroom-centered intervention was associated with higher scores on standardized achievement tests, greater odds of high school graduation and college attendance, and reduced odds of special education service use.The intervention effects of the Family-School Partnership were in the expected direction; however, only 1 effect reached statistical significance.The findings of this randomized controlled trial illustrate the long-term educational impact of preventive interventions in early elementary school.